JUSTIFICATION BY FAITH ENABLES US TO REJOICE IN TIMES OF SUFFERING - Agustinus Dermawan (Sekolah Tinggi Teologi Satyabhakti, Malang, 2023)
St. Paul's Epistle to the Romans holds a significant place in Christian theology, as it introduces essential concepts such as justification, imputation, adoption, and sanctification. While the epistle explores the theory of righteousness bestowed by God through faith in Jesus Christ, it also emphasizes the practical application of this doctrine in the lives of believers. This article aims to conduct a brief exegetical study, focusing on the practical implications of justification by faith and its relevance to the present suffering of believers. The literary and historical context of the epistle supports the authorship of the apostle Paul, as evidenced by the emphasis on justification, the understanding of Jewish perspectives, and Paul's role as the apostle to the Gentiles. By delving into the depths of this doctrine and its implications, this study aims to shed light on the transformative power of faith and its significance in the face of adversity for believers today. Abstrak Surat Rasul Paulus kepada orang-orang Roma memiliki tempat yang signifikan dalam teologi Kristen, karena memperkenalkan konsep konsep penting seperti pembenaran, imputasi, adopsi, dan pengudusan. Sementara surat ini mengeksplorasi teori kebenaran yang dianugerahkan oleh Allah melalui iman kepada Yesus Kristus, surat ini juga menekankan penerapan praktis dari doktrin ini dalam kehidupan orang percaya. Artikel ini bertujuan untuk melakukan studi eksegetis singkat, dengan fokus pada implikasi praktis dari pembenaran oleh iman dan relevansinya dengan penderitaan orang beriman saat ini. Konteks sastra dan sejarah dari surat ini mendukung kepenulisan rasul Paulus, sebagaimana dibuktikan dengan penekanan pada pembenaran, pemahaman perspektif Yahudi, dan peran Paulus sebagai rasul bagi bangsa-bangsa lain. Dengan menggali lebih dalam doktrin ini dan implikasinya, penelitian ini bertujuan untuk menjelaskan kekuatan transformatif iman dan signifikansinya dalam menghadapi kesulitan bagi orang beriman saat ini.